OP0005 Fibromyalgia in patients with rheumatoid arthritis in a 10-year perspective. (15th June 2017) - Provan, SA; Austad, C; Halsaa, V; Hammer, HB; Kvien, TK; Uhlig, T
Abstract : Background: Approximately 10% of patients with rheumatoid arthritis (RA) have coexisting fibromyalgia (FM). Little is known of the cross-sectional and longitudinal relationship between FM and RA disease activity. Objectives: To examine the cross-sectional and longitudinal relationship between FM and RA disease activity. Methods: Oslo RA register (ORAR) was established in 1994 as a prospective, observational, longitudinal nested cohort study. The inclusion criteria were RA according to the 1987-ACR classification criteria and a residential address in Oslo. 636 patients in ORAR were asked to participate in a clinical examination in 1999. A trained study-nurse systematically assessed the 18-tender point count and performed 28-tender and 28-swollen joint counts (TJC/SJC). Patients self-reported disease activity and pain related to RA, and completed the Stanford Health Assessment Questionnaire (HAQ). RA disease activity was calculated as DAS28. Fibromyalgia was diagnosed if ≥11 tender points were reported. FM associated variables; fatigue, muscular tenderness, headache, abdominal pain and difficulties concentrating were also scored (0–10 VAS). At the 10-year follow-up patients completed a questionnaire that included RA Disease Activity Index (RADAI) and Routine Assessment of Patient Index Data (RAPID-3). In cross-sectional and longitudinal analyses RA disease activity, FM associated variables and health status were compared between patients with ≥11 and <11 tender points. Level of significance was calculated using ANCOVA models corrected for age, gender, BMI and level of education. The FM associated variables at baseline were also corrected for baseline SJC 28 and C-reactive protein (CRP). The variables in the longitudinal study were corrected for the same variables as the cross-sectional analyses, but additionally for baseline values of the dependent variable when available. Results: 488 patients agreed to participate in the baseline data-collection and 192 participated at the 10-year follow-up. The mean (SD) age was 59.5 (12.5) years, and 87% were female. There were no significant differences in age, disease duration or participation at follow-up between patients with and without FM, but only women had FM. Patients with FM in addition to RA had higher DAS28, SJC, TJC, pain and patient global VAS, but also higher levels of fatigue, abdominal pain and concentration difficulties (table 1 ). At the 10-year follow-up patient with FM had significantly higher levels of RA disease activity and pain (figure 1 ). Conclusions: Presence of FM in patients with RA was associated with significantly higher levels of RA disease activity both in the cross-sectional and longitudinal perspectives. Secondary FM should be considered in patients with RA not reaching remission. Disclosure of Interest: None declared